Colorectal cancer in young patients: A case report - Rebelatto, Taiane Francieli; Bento, Luiza Haendchen; Salla, Rafaela Fenalti; Ries, Lucas Pires; Almeida, Felipe Augusto; Fior, Barbara Rayanne; Marobin, Roberta; Restelatto, Luciane; Wajner, Simone (Clinical and Biomedical Research, 2016)
The incidence of colorectal cancer is increasing in patients younger than 50 years. In this population, the disease appears to be more aggressive and advanced at the time of diagnosis, although initial symptoms are similar. Majority of the cases are sporadic tumors, but some are related to hereditary syndromes such as Lynch syndrome, which is why genetic testing is indicated. We report the case of a 17-year-old patient with colorectal cancer and no family history of bowel cancer.